La motivación organizacional y su alcance en la productividad de una empresa constructora pymes (2017)
With the present monograph is intended to publicize the different motivational theories and the most representative factors of each of them, to take into account, so that the workers of a construction company to develop their activities, with satisfaction and generate a good performance within of the organization. The issue of negative and positive psychosocial factors and the possible effects that they may have on workers was addressed, for which the survey methodology of professional and construction personnel is carried out as a research methodology. the different representative aspects by theory, in which primary information is obtained to know the weaknesses and strengths of the motivational factors implemented in some of the construction companies.